2022
DOI: 10.3390/su14073975
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Using Virtual Reality: Media Richness and Information System Successes

Abstract: Due to the COVID-19 pandemic outbreak, borders were closed, cities were blocked, and individuals went into quarantine. The market size of the tourism industry in 2020 declined by more than 70% compared to the previous year, regressing to the size it was 30 years ago. This does not mean that people’s needs for tourism have decreased. People started to use virtual reality technologies to get the experience of sightseeing even if they could not go directly to tourist attractions. Prior studies found that virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 46 publications
0
36
0
1
Order By: Relevance
“…This statement is consistent with the views of many authors (e.g., [ 49 , 50 , 51 ]) and such progress can be expected in the future [ 73 ], because digitalization plays a crucial role [ 74 ]. Even some studies found that virtual reality technology is effective for online shopping [ 75 ]. According to [ 76 ], augmented reality and virtual reality technologies have been used to improve the online shopping experience.…”
Section: Discussionmentioning
confidence: 99%
“…This statement is consistent with the views of many authors (e.g., [ 49 , 50 , 51 ]) and such progress can be expected in the future [ 73 ], because digitalization plays a crucial role [ 74 ]. Even some studies found that virtual reality technology is effective for online shopping [ 75 ]. According to [ 76 ], augmented reality and virtual reality technologies have been used to improve the online shopping experience.…”
Section: Discussionmentioning
confidence: 99%
“…According to educational research, the perceived vividness of an interactive learning environment is closely related to the learning experience of the student. Vividness is one of the core elements of media richness ( Lee 2022 ). The richer the design details of the media, the more vivid the learning environment for students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This new approach has had a great impact on tourism, especially after the COVID-19 pandemic, when cities and countries closed down, and people started to use virtual reality technologies. This also promotes future tourism, as it has been found that people have shown interest in travelling to visit the site after experiencing this type of technology [32].…”
Section: Background and Related Workmentioning
confidence: 98%